#TITLE_ALTERNATIVE# - RIADY (NIM : 13706039); Pembimbing: Ir. Ahmad Nuruddin, PhD, RADO
Barium ferrite (BaFe12O19) having hexagonal crystal structure is widely used as a permanent magnet and as an alternative material for microwave absorber due to its properties for absorbing microwave. In this report, BaFe12O19 powder was synthesized via sol-gel auto-combustion route and investigated the effect of microwave treatment to the phase formation BaFe12O19 and magnetic properties of barium ferite powder. The starting materials are pure reagent of ferric nitrat (Fe(NO3)3. 9H2O), barium nitrat (Ba(NO3)2) as the main precursors, and citric acid (CA) acts as a cheleating agent and the fuel. The molar ratio of Ba : Fe : CA are 1 : 11.5 : 25 respectively. We used Aquabidestilat to solute the starting materials and NH4OH to adjust the pH value of 3.4. The solution was thermally dehydrated to dryness in the oven. The samples were characterized by TG/DTA, FTIR, XRD, SEM, and VSM. Based on TG/DTA data interpretation, It was shown that the decomposition was happened greatly at 350oC followed by exothermic reaction. Microwave irradiation enhanced the decomposition rate and assist the formation of BaFe12O19 to about 20 w%, but insufficient to produce single phase barium ferrite. Further calcination at 900oC is required to fully eliminate the intermediate phase barium ferrite. Single phase BaFe12O19 was produced with average grain size of about 175 nm. We characterized the magnetic properties of samples using VSM. Based on the VSMÃ‚Â’s data, microwave irradiation can reduce the magnetic properties of Barium Ferrite.